Analysis of Job Satisfaction, Employee Engagement, and Turnover Intention at AUTO 2000 Body & Paint Cibiru Bandung (The Indonesian Journal of Business Administration, 2020)
AUTO 2000 Body & Paint Cibiru Bandung is a body and paint workshop facility that was built separately from the dealer. AUTO 2000 itself is a sales, maintenance, repair and supply service network for Toyota spare parts. This company has more than 60 years of experience. In the past few years, many employees have joined and left in a short period of time, so the turnover rate is highly enough. Therefore, AUTO 2000 Body & Paint Cibiru Bandung needs solutions and improvements to retain its employees.This study aims to help AUTO 2000 Body & Paint Cibiru Bandung in retaining its employees. In this study, the author conducted a field study by collecting data and information obtained from employees of AUTO 2000 Body & Paint Cibiru Bandung. There are 31 out of 36 employees (86% of the population) who participated in completing the survey. The collection of data and information was carried out by distributing questionnaires containing the approach to job satisfaction, employee engagement, and employee turnover intentions. These approaches were chosen based on previous research.Based on the results of the study, the causes of employee dissatisfaction at AUTO 2000 Body & Paint Cibiru Bandung were caused by compensation and benefits and work environment factors, while the cause of employee disengagement was due to poor relationships with co-wrokers and engagement behaviors.After knowing the causes of employee dissatisfaction and disengagement in the company, the author propose recommendations and implementation plans in accordance with company conditions in order to retain employees.Keywords: job satisfaction, employee engagement, turnover intention